2015
DOI: 10.3168/jds.2015-9571
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relationships among Enterococcus faecalis isolates from different sources as revealed by multilocus sequence typing

Abstract: Enterococcus faecalis is part of the natural gut flora of humans and other mammals; some isolates are also used in food production. So, it is important to evaluate the genetic diversity and phylogenetic relationships among E. faecalis isolates from different sources. Multilocus sequence typing protocol was used to compare 39 E. faecalis isolates from Chinese traditional food products (including dairy products, acidic gruel) and 4 published E. faecalis isolates from other sources including human-derived isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Unlike other lactic acid bacteria, enterococci are not considered GRAS (generally regarded as safe), and their presence in water is considered an indicator of faecal contamination. However, enterococci are important lactic acid bacteria in the fermented food industry due to their probiotic properties and ability to synthesise proteins with antimicrobial activity such as bacteriocin production (Klein ; Chen et al ). In addition, the use of Enterococcus strains with probiotic properties as food additives has been proposed in the International Meeting of Lactic Acid Bacteria Industrial Platform (Robinson ).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike other lactic acid bacteria, enterococci are not considered GRAS (generally regarded as safe), and their presence in water is considered an indicator of faecal contamination. However, enterococci are important lactic acid bacteria in the fermented food industry due to their probiotic properties and ability to synthesise proteins with antimicrobial activity such as bacteriocin production (Klein ; Chen et al ). In addition, the use of Enterococcus strains with probiotic properties as food additives has been proposed in the International Meeting of Lactic Acid Bacteria Industrial Platform (Robinson ).…”
Section: Introductionmentioning
confidence: 99%
“…As a species of lactic acid bacteria, E. faecalis is widely used in the production of fermented foods, particularly fermented dairy products. In recent years, numerous E. faecalis strains have been recovered from traditional dairy products [ 10 13 ]. Furthermore, water and soil are also common habitats of E. faecalis [ 14 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to other bacteria, lactic acid bacteria exchange genetic materials from the environment through horizontal gene transfer to adapt to the new environment and to survive. Chen et al [22] proposed that Enterococcus faecium in the natural fermented milk of different resources evolved to adapt to the environment. Zhang et al [23] found in the study to genetic diversity of Leuconostoc mesenteroides that isolated strains had rich genetic diversity.…”
Section: Results and Analysismentioning
confidence: 99%